Dissecting Ubiquitin Signaling with Linkage‐Defined and Protease Resistant Ubiquitin Chains1. Issue 47 (4th September 2014) - Schneider, Tatjana; Schneider, Daniel; Rösner, Daniel; Malhotra, Saurav; Mortensen, Franziska; Mayer, Thomas U.; Scheffner, Martin; Marx, Andreas
Abstract Ubiquitylation is a complex posttranslational protein modification and deregulation of this pathway has been associated with different human disorders. Ubiquitylation comes in different flavors: Besides mono‐ubiquitylation, ubiquitin chains of various topologies are formed on substrate proteins. The fate of ubiquitylated proteins is determined by the linkage‐type of the attached ubiquitin chains, however, the underlying mechanism is poorly characterized. Herein, we describe a new method based on codon expansion and click‐chemistry‐based polymerization to generate linkage‐defined ubiquitin chains that are resistant to ubiquitin‐specific proteases and adopt native‐like functions. The potential of these artificial chains for analyzing ubiquitin signaling is demonstrated by linkage‐specific effects on cell‐cycle progression.